Cornered : the new monopoly capitalism and the economics of destr uction - Lynn, Barry C. (Hoboken, N.J. : John Wiley & Sons, 2010)
Journalist Barry C. Lynn paints an alarming picture: most of our pub lic debates about globalization, competitiveness, creative destruction, and risky finance are nothing more than a cover for the widespread con solidation of power in nearly every sector of the American economy.
The hidden monopolies everywhere -- Supply and command -- The crysta l house -- The market masters -- In the cockpit -- Lightning escapes th e bottle -- The American piece -- Wreckonomics 101 -- To keep our repub lic.
Includes bibliographical references (p. 291-299) and index.
Keywords: Monopolies -- United States; Capitalism -- United States